2017
DOI: 10.3847/1538-4357/834/2/121
|View full text |Cite
|
Sign up to set email alerts
|

PHYSICAL CONTACT BETWEEN THE +20 km s−1 CLOUD AND THE GALACTIC CIRCUMNUCLEAR DISK

Abstract: This paper reports the discovery of evidence for physical contact between the Galactic circumnuclear disk (CND) and an exterior giant molecular cloud. The central 10 pc of our Galaxy has been imaged in the HCN J=1-0, HCO + J=1-0, CS J=2-1, H 13 CN J=1-0, SiO J=2-1, SO N J =2 3 -1 2 , and HC 3 N J=11-10 lines using the Nobeyama Radio Observatory 45 m radio telescope. Based on our examination of the position-velocity maps of several high-density probe lines, we have found that an emission "bridge" may be connect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 46 publications
0
21
2
Order By: Relevance
“…We do not detect, in this diagram, any feature similar to the negative-longitude extension (NLE), as visible in the longitude-velocity diagram in Fig. 1 of Takekawa et al (2017). ticular, these authors found 13 H2O masers coincident with submm continuum detected clumps and further 5 gravitationally bound clumps detected only in the submm continuum, for a total of 18 potential protostars.…”
Section: Longitude-velocity Diagramcontrasting
confidence: 46%
See 3 more Smart Citations
“…We do not detect, in this diagram, any feature similar to the negative-longitude extension (NLE), as visible in the longitude-velocity diagram in Fig. 1 of Takekawa et al (2017). ticular, these authors found 13 H2O masers coincident with submm continuum detected clumps and further 5 gravitationally bound clumps detected only in the submm continuum, for a total of 18 potential protostars.…”
Section: Longitude-velocity Diagramcontrasting
confidence: 46%
“…8 in Hsieh et al 2017 and Fig. 1 in Takekawa et al 2017) and it is coherent with the orbital motion of the cloud (i.e., the CND is corotating with the +20 km/s cloud). The infalling molecular cloud is occupying the right part of the PV diagram, with a median line-of-sight velocity of roughly +20 km/s, though with a moderately larger spread in velocity, compared to the observations.…”
Section: Longitude-velocity Diagrammentioning
confidence: 60%
See 2 more Smart Citations
“…• 088. The emission layer distributed over V LSR 10 to 40 km s −1 is from M-0.13-0.08 (also referred to as the 20 km s −1 cloud), which probably lies immediately in front of the circumnuclear disk (e.g., Takekawa et al 2017a). T1 has the broadest velocity width, which reaches up to ∆V ∼ 100 km s −1 in full width at zero intensity, showing a remarkably steep velocity gradient.…”
Section: Spatial and Velocity Structurementioning
confidence: 99%